Progress in Research on the Role of FGF in the Formation and Treatment of Corneal Neovascularization - Chen, Mengji; Bao, Licheng; Zhao, Mengying; Cao, Jiarong; Zheng, Haihua (Frontiers in Pharmacology, 2020)
Corneal neovascularization (CNV) is a sight-threatening disease usually associated with inflammatory, infectious, degenerative, and traumatic disorders of the ocular surface. Fibroblast growth factor (FGF) plays a strong role in angiogenic to induce corneal neovascularization, which has significant effect on the differentiation, proliferation, metastasis and chemotaxis of vascular endothelial cells. Both acidic fibroblast growth factor (aFGF) and basic fibroblast growth factor (bFGF) have been proved positive staining in the capillaries which was induced among the corneal stromal cells. The degree of endothelial cell differentiation induced by bFGF in corneal neovascularization is not high, but the anabolism is active. FGFs exert their effects via specific binding to cell surface-expressed specific receptors. In this article we believe that both anti-FGF antibodies and anti-FGF receptor antibodies can be new directions aim to the treatment of CNV. Similar to anti-VEGF antibodies, subconjunctival injection and eye drops can be considered as effective form of drug delivery.